1984
DOI: 10.1111/j.2042-3306.1984.tb01895.x
|View full text |Cite
|
Sign up to set email alerts
|

A field trial of ketamine anaesthesia in the horse

Abstract: Summary Ketamine was used on 80 occasions to induce anaesthesia in 77 animals. Xylazine premedication was used alone on 75 occasions, in conjunction with methadone once, in conjunction with methadone and acepromazine once and, on three occasions, methadone and acepromazine only were used. Anaesthesia was maintained in seven cases with halothane and oxygen. Premedication with xylazine 5 mins previously or concurrently with ketamine gave similar results but an interval of more than 5 mins between the drugs produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Dosages of ketamine and thiopental in the current study were selected based on published values , and these dosages have been routinely used in our clinical practice. However, dosage of alfaxalone was based on the results of preliminary experimental studies at our institute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dosages of ketamine and thiopental in the current study were selected based on published values , and these dosages have been routinely used in our clinical practice. However, dosage of alfaxalone was based on the results of preliminary experimental studies at our institute.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is a dissociative anaesthetic widely used in equids as an induction agent and in total intravenous anaesthesia. With appropriate premedication, ketamine produces rapid and smooth induction with minimal cardiovascular depression and good analgesia . However, excitement, transient ataxia, and muscular tremors and rigidity during the recovery phase can occur with intravenous ketamine .…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic induction in the study reported here was extremely sudden and differed from the smooth anesthetic inductions usually seen with ketamine in which horses slowly assume sternal recumbency and then lateral recumbency. 24 As a result of this, for some horses (eg, horses with fractures that cannot be stabilized prior to induction), the use of propofol as an induction agent cannot be recommended. Endotracheal intubation, on the other hand, was always easily accomplished with propofol, a fact that also has been reported in human anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…). For extremely painful procedures, methadone (Methadone Hydrochloride), with and without acepromazine (PromAce) was administered to enhance analgesia during xylazine and ketamine anaesthesia (Parsons and Walmsley ; Fisher ).…”
Section: Clinical Usesmentioning
confidence: 99%
“…Central nervous system stimulation characterised by hyperresponsiveness and spasmodic lip movements were reported in excitable individuals after butorphanol administration, whereas deep sedation and ataxia were observed in a Belgian stallion (Tranquilli et al 1983). For extremely painful procedures, methadone (Methadone Hydrochloride) 6 , with and without acepromazine (PromAce) 7 was administered to enhance analgesia during xylazine and ketamine anaesthesia (Parsons and Walmsley 1982;Fisher 1984).…”
Section: Horsesmentioning
confidence: 99%